[Steam Along Buildings] - Streng, Evelyn Fiedler (1975)
Photograph of steam outside buildings. Small white buildings with grey doors sit along a dark street where a group of people walk. A larger white building sit to the left with lines of thin, dark windows. Steam shoots up from a ditch beside the street, obscuring the buildings behind it. A large building with a red roof is visible in the background ahead of a dark mountain.